1992
DOI: 10.1159/000247489
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nonfamilial and Familial Melanoma

Abstract: There has been concern that individuals with nonfamilial melanoma and dysplastic melanocytic nevi (DMN) are not directly comparable to patients with hereditary melanoma and DMN. Because we have conducted a comprehensive study of nonfamilial melanoma over the past several years, we have addressed the above issue by directly comparing the characteristics of 145 nonfamilial patients, 6 patients with familial melanoma and the information available for familial melanoma in the literature. All 6 patients with famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…The number of naevi was, on average, significantly greater in familial cases, and this is particularly evident for the ‘great naevi’ and the clinically atypical naevi, especially those located on the trunk and the lower limb (data not shown). In the literature, the evaluation of nevi in familial vs. sporadic melanomas was analysed, although partially and with conflicting results, in a small number of studies 2,9,20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of naevi was, on average, significantly greater in familial cases, and this is particularly evident for the ‘great naevi’ and the clinically atypical naevi, especially those located on the trunk and the lower limb (data not shown). In the literature, the evaluation of nevi in familial vs. sporadic melanomas was analysed, although partially and with conflicting results, in a small number of studies 2,9,20 …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the evaluation of nevi in familial vs. sporadic melanomas was analysed, although partially and with conflicting results, in a small number of studies. 2,9,20 We could wonder whether the higher number of melanocytic naevi, either great or atypical ones, depends on more numerous sunburns or is an independent factor in relationship with a genetic pressure responsible for a higher melanocytic cell proliferation, possibly, for an earlier melanoma growth. A large number of naevi and of atypical naevi in high risk kindreds with CDKN2A mutation was considered to be caused by a responsible gene.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the actual melanomas in family members are histiologically indistinguishable from sporadic melanomas and have similar prognosis. Family members with melanoma, however, usually have an earlier age of onset, have thinner melanomas detected, and are more likely to develop multiple primary melanomas (Kopf et al, 1986;Barnhill et al, 1992). A meta-analysis of eight case-control studies from Europe, Australia, and North America revealed that family history of melanoma among individuals with melanoma varied by geographic area from 0.6 to 12.5%, with generally higher percentages in areas of higher melanoma incidence .…”
Section: Family Historymentioning
confidence: 99%
“…6,7 However, the occurrence of melanoma in pediatric (<20 years) members of these families has not been fully investigated. The goal of the current study was to evaluate the occurrence and clinical and genetic characteristics of young onset (i.e.…”
Section: Introductionmentioning
confidence: 99%